Les voyelles intermédiaires : des questions de normativité, usage et enseignement - Rubio, Marcela (2021)
This article introduces some reflections about the phonolo gical status of vowels /e, ε, ø, œ, o, ͻ/ and how to teach them. These vocalic sounds constitute a particular instance of the French phonological system because of their articulatory and acoustic natur e, their realizations and the constrains that affect them. The starting point of research done in various relevant con texts, from acoustic phonetics (Lauret, 2007 ; Vaissière, 2011 ; Billières 2014) to phonestilistics (Léon 1993, 2011) and sociophonetics approaches (Candea & Trimaille 2015, Østby 2016). A discussion of the goals of learning is included along with a situated reflection upon our teaching context. This article also s uggests an abridged vocalic system, derived from the simplification of the degre es of openness.